2019
DOI: 10.1002/ijgo.12831
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of Robson 10‐group classification system and poverty in southern and southeastern Brazil

Abstract: Objective To assess the spatial distribution of the Robson 10‐group classification system (TGCS) and poverty in southeastern and southern regions of Brazil in 2016. Methods An ecologic study based on public data from the Brazilian Information System on Live Births and the Brazilian Institute of Geography and Statistics, including 1 519 289 (53.2%) of all live‐born neonates in Brazil between January and December 2016. Statistical analysis used Bayesian modelling with spatial distribution following an autoregres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Based on the current results, the cesarean section rate in the HUSM is higher than that found in other national and international studies, but it is similar to the rate recorded for the state, as reported by Brunherotti et al (2019), 25 who found a cesarean section rate of 60.7% in Southern Brazil. Since Group 5 presents a larger number of cesarean sections than the other groups, and since the incidence of previous cesarean section is the main indication for cesarean sections, it is necessary to take actions focused on changing the current scenario, mainly on raising the awareness about first cesarean section avoidance when it is not really necessary.…”
Section: Discussionsupporting
confidence: 87%
“…Based on the current results, the cesarean section rate in the HUSM is higher than that found in other national and international studies, but it is similar to the rate recorded for the state, as reported by Brunherotti et al (2019), 25 who found a cesarean section rate of 60.7% in Southern Brazil. Since Group 5 presents a larger number of cesarean sections than the other groups, and since the incidence of previous cesarean section is the main indication for cesarean sections, it is necessary to take actions focused on changing the current scenario, mainly on raising the awareness about first cesarean section avoidance when it is not really necessary.…”
Section: Discussionsupporting
confidence: 87%
“…In Brazil, the Robson classification system has been previously applied in the national “Birth in Brazil” cohort [ 7 ], and some hospital-based studies in Sao Paulo [ 8 ] and Brasilia [ 9 ]. Using routinely collected birth registration data, the objectives of our study were to (1) estimate the caesarean rate in Brazil stratified by Robson category, (2) assess the extent to which caesarean sections were clinically indicated, and (3) identify any variation across different socioeconomic groups.…”
Section: Introductionmentioning
confidence: 99%
“…A recent ecological study showed that in Brazil, the frequencies of each group of the RTGCS are heterogeneously distributed in the geographic space, with meaningful associations with the proportion of poverty in the different regions [5].…”
Section: Introductionmentioning
confidence: 99%